Polymorphisms of RS7055763 and RS41307258 in TBX22 Gene Haplotype as Risk Factors for Non-syndromic Cleft Palate Indonesian Deutero-Malay Population - Susanti, Nita; Ullah, Irfan; Sulaksono, Haura Labibah Salsabil; Nasroen, Saskia Lenggogeni; Maskoen, Ani Melani (Universitas Islam Bandung, 2024)
Non-syndromic cleft palate (NS-CP) is a multifactorial congenital malformation affected by genetic and environmental factors. The incidence of non-syndromic cleft lip with or without cleft palate (NS-CLP) varies considerably between ethnic groups and geographical regions. TBX22 is a crucial determinant for the formation of intramembranous bone in the posterior hard palate. Therefore, TBX22 is fundamental to palatogenesis and supports normal palate progress. The rs7055763 and rs41307258 polymorphisms in the TBX22 gene are associated with risk factors for NS-CP in the Indonesian Deutero-Malay population. In the previous study, NS-CP still needed to be investigated in the Deutero-Malay population. However, there are different races, mainly for the Deutero-Malay population. This study aims to determine whether rs7055763 and rs41307258 polymorphisms in the TBX22 gene are risk factors for NS-CP in the Deutero-Malay population. This study was conducted in Terpadu Laboratory, Faculty of Dentistry, Universitas Padjadjaran, from February until June 2023. The design of this study was a case-control study. The DNA patient samples were obtained from saliva and whole blood. Moreover, DNA is extracted, and the rs7055763 and rs41307258 segments are analyzed using PCR and Sanger sequencing. PCR data was analyzed by chi-square testing. In this study analysis, polymorphisms of rs7055763 (G>A) and rs41307258 (T>A) in the TBX22 gene show no significant differences between case and control groups, namely 0.911 and 0.645, respectively. However, the genotype in the rs41307258 shows the p-value as 0.027, indicating substantial differences and the OR is 1.390. In conclusion, the rs7055763 and rs41307258 polymorphisms in the TBX22 gene do not appear to be risk factors for developing NS-CP in the Indonesian Deutero-Malay population.